Strategi BKM Mesjid Ar-Rahman dalam Meningkatkan Partisipasi Remaja pada Kegiatan Keagamaan di Desa Peria-Ria Kecamatan Biru-Biru - Rudin, Sapar; Parianto, Parianto; Alawiyah, Tuti (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This research aims to analyze the strategies employed by the Ar-Rahman Mosque Prosperity Board (BKM) in enhancing youth participation in religious activities at Peria-Ria Village, Biru-Biru District. The study investigates the methods and approaches used by BKM to engage the youth, considering the unique socio-cultural context of the village. Through qualitative research methods, including interviews and observations, this study explores the effectiveness of various BKM initiatives, such as educational programs, community service, and recreational activities, in fostering a stronger connection between the youth and the mosque. The findings highlight the importance of tailored strategies that resonate with the youth's interests and needs, and underscore the role of BKM in creating a supportive and inclusive environment. This research contributes to understanding the dynamics of youth engagement in religious activities within rural communities, offering insights for mosque management and community development.